Factors associated with refusal to participate in HIV surveillance in rural KwaZulu Natal, South Africa - Mthethwa, Ncengani Abigail Celani (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.